2020
DOI: 10.3390/nu12010222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Synbiotic Supplement on Human Gut Microbiota, Body Composition and Weight Loss in Obesity

Abstract: Targeting gut microbiota with synbiotics (probiotic supplements containing prebiotic components) is emerging as a promising intervention in the comprehensive nutritional approach to reducing obesity. Weight loss resulting from low-carbohydrate high-protein diets can be significant but has also been linked to potentially negative health effects due to increased bacterial fermentation of undigested protein within the colon and subsequent changes in gut microbiota composition. Correcting obesity-induced disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
137
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(147 citation statements)
references
References 57 publications
5
137
0
5
Order By: Relevance
“…and Bifidobacterium spp. requires extended validation methods, culturing [ 86 ] or molecular methods [ 87 ] to evidence the correlation of probiotics-microbiota-BMI modifications [ 88 ]; however, it remains controversial whether detection of this species is associated with the microbiota modification [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…and Bifidobacterium spp. requires extended validation methods, culturing [ 86 ] or molecular methods [ 87 ] to evidence the correlation of probiotics-microbiota-BMI modifications [ 88 ]; however, it remains controversial whether detection of this species is associated with the microbiota modification [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Examples are given in Table 1 , which focuses on RCTs demonstrating benefits. Null trials have also been published across a variety of outcomes, including, for example, some studies aimed at the prevention of surgical infections 39 , 40 , treatment of obesity 41 , management of gestational diabetes mellitus 42 and eradication of Helicobacter pylori infection 43 , 44 . However, evidence of a health benefit is not in itself sufficient to call a formulation of live microorganism(s) plus selectively utilized substrate(s) a ‘synbiotic’.…”
Section: Current Levels Of Evidencementioning
confidence: 99%
“…Evidence supporting the health-promoting effects of probiotics in healthy adults is limited and less consistent [ 10 , 11 , 12 ]. Although many studies have investigated correlations with specific blood markers by targeting a single strain to observe disease associations, the findings of these studies might result from numerous confounding factors [ 13 ]. There are also differences in microbial strains, viable cell concentrations, and probiotic product formulations [ 14 ], and most studies only controlled some factors affected by these variables.…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies demonstrating the effectiveness of synbiotics [ 13 , 21 , 22 , 23 ]. Several studies have shown that the use of synbiotics has superior benefits over probiotics or prebiotics alone.…”
Section: Introductionmentioning
confidence: 99%